Analysis of physics teaching module development competency among prospective physics teachers from the perspective of the merdeka belajar curriculum - Poernomo, Joko Budi; Sadad, Imam Akmal; Jannah, Miftakhul; Sugito, Sugito (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
The competency of pre-service physics teachers in developing teaching modules based on the Merdeka Curriculum serves as a crucial indicator of pedagogical readiness in the era of differentiated learning. This study primarily focuses on the quality of time allocation planning and learning activity structure. A quantitative descriptive-comparative method was employed to evaluate 52 physics teaching modules created by physics education students, assessed by four expert validators. Results indicate an average competency score of 3.06 (moderate category) in an Indonesian university, with notable weaknesses in time allocation (score=2.76) and learning sequence design (score=2.73). Approximately 25% of modules demonstrated disproportionate time allocation (70-80% dedicated to core activities), while 53.5% exhibited illogical activity sequencing. Comparative analysis revealed a significant difference between Group A (score=3.21) and Group B (score=2.85) (t=3.12, p<0.01). This study recommends integrating digital tools and implementing iterative microteaching to strengthen holistic and differentiated instructional design competencies. The findings advocate for evidence-based reorientation of teacher education curricula.